An Evaluation of the Cancer Support Specialist Service in Children's Health Ireland - Murphy, Maryanne; Higgins, Agnes (Trinity College Dublin, 2024)
There has been increasing recognition of the psychological impact of a cancer diagnosis not just on the child, but on the entire family and the wider community. The onset of childhood cancer is sudden and unexpected, and the effect on the family unit can be enormous as they embark on a major life transition. Families of children with cancer have a high level of psychosocial needs due to the many challenges they may face during their child’s cancer journey. However, previous research, including phase one of the Katie Nugent research project, indicates that the current healthcare system does not always meet these needs. In response to this, Cancer Support Specialist Service is being introduced as a partnership between the Katie Nugent Fund at Children’s Health Foundation, Children’s Health Ireland at Crumlin and the Cancer Fund for Children to provide informal psychosocial support to families of children with cancer. During the period of introduction of the service, five cancer support specialist roles were appointed throughout the Republic of Ireland, providing support to families in St. John’s Ward in Children’s Health Ireland at Crumlin and in the community in Leinster, Munster, the midlands, and Connaught. The aim of the study was to explore the implementation and impact of the Cancer Support Specialist Service from the perspective of the key stakeholders involved.
PUBLISHED
Keywords: Cancer; CHILDHOOD CANCERS; Other; Children